Tetris : the games people play - Brown, Box (First Second, 2016)
"It is, perhaps, the perfect video game. Simple yet addictive, Tetris delivers an irresistible, unending puzzle that has players hooked. Play it long enough and you'll see those brightly colored geometric shapes everywhere. You'll see them in your dreams. Alexey Pajitnov had big ideas about games. In 1984, he created Tetris in his spare time while developing software for the Soviet government. Once Tetris emerged from behind the Iron Curtain, it was an instant hit. Nintendo, Atari, Sega--game developers big and small all wanted Tetris. A bidding war was sparked, followed by clandestine trips to Moscow, backroom deals, innumerable miscommunications, and outright theft. In this graphic novel, New York Times--bestselling author Box Brown untangles this complex history and delves deep into the role games play in art, culture, and commerce. For the first time and in unparalleled detail, Tetris: The Games People Play tells the true story of the world's most popular video game."--Page [2] of cover.